COVID-19 Perceptional Disparity Among Dental Healthcare Personnel at King Faisal University: Applying Health Belief Model - Nasir, Elwalid Fadul; Elhag, Ahmed Khalid; Almahdi, Hatim Mohammed (European Journal of Dentistry, 2020)
Objectives In Saudi Arabia, more than 100, 000 cases of COVID-19 have been reported, and more than 4,000 in Al Hofuf to date. Dental healthcare personnel are at a higher risk of COVID-19 due to their exposure to saliva, blood, and aerosol/droplet during their daily practice. Their perceptions of COVID-19 drive their behaviors.Materials and Methods A cross-sectional online survey to assess COVID-19 related perceptions and possible disparities between them.Statistical analysis Data were analyzed using the Statistical Package for the Social Science, version 23 (IBM SPSS). Descriptive analyses were performed using frequencies and percentages for categorical variables, mean and (± SD) for numerical variables. Bivariate analyses were assessed using t-test and one-way ANOVA, with a 95% confidence interval (CI).Results With a response of 75% (150), results showed that there were perceptional disparities: students and technical staff perceived more barriers to preventive measures compared to faculties with a mean difference of (−0.145 SD ± 0.580, p = 0.802, CI −1.29 / 1.00 and −2.433, SD ± 0.94, p = 0.010), respectively. This was also shown in threat perception with a mean difference of (2.525, SE ± 0.917, CI 0.71/4.34, p = 0. 0.007). Students perceived more threat than clerks did with a mean difference of (1.281, SE ± 0.569, CI − 0.16 / 2.41, p = 0.026), while clerks perceived less threat than the technical staff with a mean difference of (−2.790, SE ± 0.860, CI −4.49 /−1.09, p = 0.001).Conclusions There was a clear disparity in the perceptions among the different categories of participants. More emphasis on the training and preparedness of the dental healthcare personnel is required.
Keywords: COVID-19; health belief model; perception; self-efficacy; severity